Language Games recategorised - Kalmár Lenke (2007)
My thesis examines the English language games from a quite unusual point of view. It points out what principles of game pedagogy must be taken into consideration when using language games in ELT. I will emphasise how games from our childhood and language games are related to each other. Furthermore, the recategorisation of language games offers a quite new picture of them.